Multiverse Ethnography : A replication and recontextualization as an audience study - Kauraoja, Valtteri (My University, 2023)
This study is a conceptual replication of an exploratory study introducing a new method for the study of interactive media (Karhulahti et al. 2022). Multiverse Ethnography tasks a team of researchers to write fieldwork journals that are coded and subsequently analysed to create a design of thematic structures presenting the findings of the study. The original study concerned Cyberpunk 2077 (CD Projekt RED, 2020) and Among Us (Innersloth, 2018), tasking a class studying game studies-methodology with the fieldwork and a co-operative coding process. As a more contained study with a single researcher, this replication excludes Cyberpunk 2077. The participants writing fieldwork journals did not have an academic role in the study, as it lacked the classroom context. The contextual differences of the data collection seemed to lead to fewer hours of interaction, possibly causing players to write down less observations of emergent meta-strategies or changes in the form of updates and customization. This would identify such themes as increasing in relevance relative to player’s experience. Comparative applications of the method are encouraged, as differences between different language game servers were identified. All elements of the thematic clusters emerging in the original study were identified in the data for the replication, though some themes lost relevance possibly because of these contextual factors. Applying the method as a solo researcher is not recommended, due to the large workload of data collection and the increased validity offered by co-operative coding and analysis.
Keywords: ethnography, methodology, digital culture, qualitative research